Changes in self-reported and parent-reported health-related quality of life in overweight children and adolescents participating in an outpatient training: findings from a 12-month follow-up study - Finne, Emily (BioMed Central, 2013)
BACKGROUND: Health-related quality of life (HRQoL) was found to improve in participants of weight management interventions. However, information on moderately overweight youth as well as on maintaining HRQoL improvements following treatment is sparse. We studied the HRQoL of 74 overweight, but not obese participants (32.4% male, mean age = 11.61 ± 1.70 SD) of a comprehensive and effective six-month outpatient training at four time-points up to 12 months after end of treatment. METHODS: HRQoL was measured by self-report and proxy-report versions of the generic German KINDL-R, including six sub domains, and an obesity-specific additional module. Changes in original and z-standardized scores were analyzed by (2×4) doubly multivariate analysis of variance. This was done separately for self- and proxy-reported HRQoL, taking into account further socio-demographic background variables and social desirability. Additionally, correlations between changes in HRQoL scores and changes in zBMI were examined. RESULTS: There were significant multivariate time effects for self-reported and proxy-reported HRQoL and a significant time-gender interaction in self-reports revealed (p < .05). Improvements in weight-specific HRQoL were evident during treatment (partial η(2) = 0.14-0.19). Generic HRQoL further increased after end of treatment. The largest effects were found on the dimension self-esteem (partial η(2) = 0.08-0.09 for proxy- and self-reported z-scores, respectively). Correlations with changes in weight were gender-specific, and weight reduction was only associated with HRQoL improvements in girls. CONCLUSIONS: Positive effects of outpatient training on generic and weight-specific HRQoL of moderately overweight (not obese) children and adolescents could be demonstrated. Improvements in HRQoL were not consistently bound to weight reduction. While changes in weight-specific HRQoL were more immediate, generic HRQoL further increased after treatment ended. An extended follow-up may therefore be needed to scrutinize HRQoL improvements due to weight management. TRIAL REGISTRATION: clinicaltrials.gov NCT00422916